2017
DOI: 10.4049/jimmunol.1700253
|View full text |Cite
|
Sign up to set email alerts
|

IL-20 Signaling in Activated Human Neutrophils Inhibits Neutrophil Migration and Function

Abstract: Neutrophils possess multiple antimicrobial mechanisms that are critical for protection of the host against infection with extracellular microbes, such as the bacterial pathogen Staphylococcus aureus. Recruitment and activation of neutrophils at sites of infection is driven by cytokine and chemokine signals that directly target neutrophils via specific cell surface receptors. The IL-20 subfamily of cytokines has been reported to act at epithelial sites and contribute to psoriasis, wound healing, and anti-inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 47 publications
2
24
1
Order By: Relevance
“…Using an in vitro model of PMN migration, Gough et al . recently demonstrated that IL-20 actively inhibits PMN transmigration across bronchoepithelial cells in an ERK1/2 dependent fashion [53]. A similar IL-20 mediated inhibition of PMN trafficking has been reported in vivo in a mouse model of corneal healing [54].…”
Section: Introductionmentioning
confidence: 60%
See 3 more Smart Citations
“…Using an in vitro model of PMN migration, Gough et al . recently demonstrated that IL-20 actively inhibits PMN transmigration across bronchoepithelial cells in an ERK1/2 dependent fashion [53]. A similar IL-20 mediated inhibition of PMN trafficking has been reported in vivo in a mouse model of corneal healing [54].…”
Section: Introductionmentioning
confidence: 60%
“…Recently Gough et al found that IL-20 inhibits PMN phagocytosis, degranulation and migration by modifying actin polymerization in an S. aureus model of infection [53]. IL-20 signals through two different receptor complexes made up of heterodimers of the common IL-20RB subunit and either IL-20RA (complex type I) or IL-22RA (type II).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transgenic mice overexpressing IL-20 or IL-24 display some epidermal hyperplasia, although those overexpressing IL-19 do not (He and Liang, 2010). Interestingly, all three cytokines have been associated with both pro-and anti-inflammatory functions, depending on their context and/or study (Autieri, 2018;Cantó et al, 2014;Caparró s and Frances, 2018;Fujimoto et al, 2017;Gough et al, 2017;Horiuchi et al, 2015;Kako et al, 2016;Kragstrup, 2016;Kumar et al, 2018;Matsuo et al, 2015;Myles et al, 2013;Niess et al, 2018;Steinert et al, 2017;Xie et al, 2016). The in vivo roles of IL-19, IL-20, and IL-24 in psoriatic inflammation warrant further investigation.…”
Section: Introductionmentioning
confidence: 99%